Traditional Word-of-Mouth antecedents, attitudes and purchase intentions: A case of Vietnam’s infant formula product - Mai, Ngoc Phuong (2018)
Regardless the acknowledged impact of Word-of-Mouth communication on the buying decision-making process, studies examining how Word-of-Mouth recipients utilise such information is scarce. Therefore, this study exhibits a framework which comprises of various elements having impacts on the recipients’ use of Word-of-Mouth communication and the respective results of the use of Word-of-mouth within the buying intentions of recipients. The empirical evidences derived from the framework examination illustrates that characters of the Word-of-Mouth source (namely trustworthiness, expertise and experience) strongly influence the usage of Word-of-Mouth communication in face-to-face setting. Additionally, the finding affirms a strong and positive relationship between the use of Word-of-Mouth communication and attitudes toward the infant formula milk products. Theoretical and managerial contributions for researchers and practitioners are provided with guidelines for further research.